Penggunaan Teknik Permainan Kartu Watak Dalam Pembelajaran Drama Pada Siswa Kelas XI SMAN 1 Jatisari - Pramesta, Malvin Regi; Maspuroh, Uah; Adham, M. Januar Ibnu (Jurnal Ilmiah Wahana Pendidikan, 2024)
Speaking is a person's second language activity in language life after listening. With speaking skills, along with the ability to express thoughts, it is necessary to have optimism at first. To deepen or sharpen these skills, suggestions are needed that reach their achievement through the application of a supporting foundation of language skills. As well as speaking skills. One of them is in the role play or acting. Rarely do people do it just for free. Even if the drama is considered interesting, the results are good. In order to achieve his expertise, a method is needed that can foster the mentality of art in theatre. In carrying out a play, speaking skills tend to be handled in a variety of ways.